The ratio of FoxA1 to FoxA2 in lung adenocarcinoma is regulated by LncRNA HOTAIR and chromatin remodeling factor LSH - Wang, Ranran (Sci Rep, 2015)
The lncRNA HOTAIR is a critical regulator of cancer progression. Chromatin remodeling factor LSH is critical for normal development of plants and mammals. However, the underlying mechanisms causing this in cancer are not entirely clear. The functional diversification of the FOXA1 and FOXA2 contributes to the target genes during evolution and carcinogenesis. Little is known about the ratio of FOXA1 to FOXA2 in cancer. We here found that both HOTAIR and LSH overexpression was significantly correlated with poor survival in patients with lung adenocarcinoma cancer (ADC). Also, the ratio of FOXA1 and FOXA2 is linked with poor survival in patients with lung ADC. HOTAIR regulates the ratio of FOXA1 to FOXA2 and migration and invasion. HOTAIR and the ratio of FOXA1 to FOXA2 are negatively correlated. HOTAIR knockdown inhibits migration and invasion. HOTAIR is associated with LSH, and this association linked with the binding of LSH in the promoter of FOXA1, not FOXA2. Targeted inhibition of HOTAIR suppresses the migratory and invasive properties. These data suggest that HOTAIR is an important mediator of the ratio of FOXA1 and FOXA2 and LSH involves in, and suggest that HOTAIR inhibition may represent a promising therapeutic option for suppressing lung ADC progression.